A phenomenological study of preschool teachers’ experiences and perspectives on inclusion practices - Jeanice P. Bryant (Cogent Education, 2018)
Today, the inclusion of special needs children into preschool classes is fully expected; however, the logistics and best practices for ensuring the success of inclusive classrooms are not fully understood by educators. The goal of this study was to address this lack of understanding among educators. This study used a narrative, phenomenological method to explore in-depth preschool teachers’ experiences and perspectives on preschool inclusion. Eight general education preschool teachers from the author’s school district in southeastern Virginia were interviewed using an open-ended interview format. The major themes that emerged from these interviews included the general need for a better understanding of the role preschool teachers perform in the educational environment. The participants shared with the researcher that many parents and others outside of the school environment consider preschool teachers as little more than babysitters. Another theme that emerged was that more training is needed, both formal and on-the-job training, in the area of inclusion practices, as this would increase the comfort level of preschool teachers with these practices. Additional themes revealed that the attitudes of both teachers and outsiders also impact the effectiveness of preschool inclusion practices, and all of the participants reported having positive attitudes about teaching in an inclusive environment. The information obtained in this study provides us with a better understanding of preschool teachers’ experiences and perspectives about preschool inclusion. It also provides insight into what teachers may need to improve preschool inclusion.